A correlation between intestinal microbiota dysbiosis and osteoarthritis. Issue 1 (January 2019) - Szychlinska, Marta Anna; Di Rosa, Michelino; Castorina, Alessandro; Mobasheri, Ali; Musumeci, Giuseppe
Abstract: Osteoarthritis (OA) is a degenerative disease of the articular cartilage, resulting in pain and total joint disability. Recent studies focused on the role of the metabolic syndrome in inducing or worsening joint damage suggest that chronic low-grade systemic inflammation may represent a possible linking factor. This finding supports the concept of a new phenotype of OA, a metabolic OA. The gut microbiome is fundamental for human physiology and immune system development, among the other important functions. Manipulation of the gut microbiome is considered an important topic for the individual health in different medical fields such as medical biology, nutrition, sports, preventive and rehabilitative medicine. Since intestinal microbiota dysbiosis is strongly associated with the pathogenesis of several metabolic and inflammatory diseases, it is conceivable that also the pathogenesis of OA might be related to it. However, the mechanisms and the contribution of intestinal microbiota metabolites in OA pathogenesis are still not clear. The aim of this narrative review is to review recent literature concerning the possible contribution of dysbiosis to OA onset and to discuss the importance of gut microbiome homeostasis maintenance for optimal general health preservation.